Petrochemical machinery insights - Bloch, Heinz P., 1933- (Butterworth-Heinemann, 2016)
Petrochemical Machinery Insights is a priceless collection of solutions and advice from Heinz Bloch on a broad range of equipment management themes, from wear to warranty issues, organizational problems and oil mist lubrication, and professional growth and pre-purchase of machinery. The author draws on his industry experience to hone in on important problems that do not get addressed in other books, providing actionable details that engineers can use. Mechanical, reliability, and process engineers will find this book the next best thing to having Heinz Bloch on speed dial. Focuses on pieces of hard-won experience from the industry that are rarely included in other booksPresents not just a guide to technical problems, but also to crucial themes in management and organizationIncludes an informal and honest style, making author Heinz Bloch's 40 years of experience accessible to a broad audience of readersContains a uniting theme that successful asset management requires the separation of application and implementation details.